2022
DOI: 10.3390/app12147079
|View full text |Cite
|
Sign up to set email alerts
|

Cold Storage Media versus Optisol-GS in the Preservation of Corneal Quality for Keratoplasty: A Systematic Review

Abstract: Optisol-GS is the most widely used pharmaceutical composition to preserve corneas for transplantation. This systematic review investigated the effects of different cold corneal storage media (CCSM) compared with Optisol-GS on the quality of stored corneas. The literature was searched throughout May 2022 on six databases and grey literature. Studies including corneas (population) exposed to distinct cold storage media (exposure) and Optisol-GS (comparison) that reported qualitative and/or quantitative parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…8 The presence of 2 mM glutamine as a supplement in the Eusol-C has been proposed to act as a compensating factor for the absence of the additives that are otherwise present in Optisol-GS. 8,9 Eusol-C has been shown to be comparable to Optisol-GS as a cold storage solution for up to 7 days, as shown by the analysis of the donor grafts' endothelial health, stromal edema, and Descemet folding. 10 Camposampiero et al 11 demonstrated that ECD preservation of the donor grafts stored in Eusol-C for up to 2 days was found to be similar to that of donor grafts preserved in Optisol-GS.…”
Section: Outcomes Of Keratoplastymentioning
confidence: 99%
See 4 more Smart Citations
“…8 The presence of 2 mM glutamine as a supplement in the Eusol-C has been proposed to act as a compensating factor for the absence of the additives that are otherwise present in Optisol-GS. 8,9 Eusol-C has been shown to be comparable to Optisol-GS as a cold storage solution for up to 7 days, as shown by the analysis of the donor grafts' endothelial health, stromal edema, and Descemet folding. 10 Camposampiero et al 11 demonstrated that ECD preservation of the donor grafts stored in Eusol-C for up to 2 days was found to be similar to that of donor grafts preserved in Optisol-GS.…”
Section: Outcomes Of Keratoplastymentioning
confidence: 99%
“…Eusol-C contains gentamicin sulfate and dextran-components that are also present in Optisol-GS. A noteworthy difference between the 2 solutions is the absence of streptomycin sulfate, ascorbic acid, and chondroitin sulfate in Eusol-C. 8 In addition, Optisol-GS also contains nonessential amino acids, purines, and lipid components with antioxidant action. These additives, along with an increased concentration of chondroitin sulfate, were believed to contribute to the preservation and reduction of the rate of vacuolization of endothelial cells.…”
Section: Outcomes Of Keratoplastymentioning
confidence: 99%
See 3 more Smart Citations